2003
DOI: 10.1093/jmicro/52.6.593
|View full text |Cite
|
Sign up to set email alerts
|

Expression of extracellular matrix molecules, MMPs and TIMPs in alveolar bone, cementum and periodontal ligaments during rat tooth eruption

Abstract: Tooth eruption involves extensive degradation and reorganization of extracellular matrix (ECM) components. It is not known how ECM-degrading enzymes are coordinated with each other or how they are regulated in the event. The present study was designed to investigate mRNA expression of inhibitors of metalloproteinases (TIMPs) in comparison with matrix metalloproteinases (MMPs) as well as ECM molecules during rat first molar eruption using in situ hybridization. We also examined how TIMPs are involved in the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0
9

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 0 publications
3
23
0
9
Order By: Relevance
“…Osteoblasts and osteocytes may play a role in remodeling of the ECM during bone healing by coordinating the production and degradation of ECM proteins. Similar observations have been reported during bone development Tsubota et al, 2002;Maruya et al, 2003;Nakamura et al, 2005;Sone et al, 2005) and during appositional bone formation (Hatori et al, 2004).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Osteoblasts and osteocytes may play a role in remodeling of the ECM during bone healing by coordinating the production and degradation of ECM proteins. Similar observations have been reported during bone development Tsubota et al, 2002;Maruya et al, 2003;Nakamura et al, 2005;Sone et al, 2005) and during appositional bone formation (Hatori et al, 2004).…”
Section: Discussionsupporting
confidence: 87%
“…MMPs 2, 8, and 13 have been implicated in the degradation of ECM during bone development (Gack et al, 1995;Mattot et al, 1995;Chin and Werb, 1997;Johansson et al, 1997;Sasano et al, 2002;Maruya et al, 2003). MMPs 2, 8, 9, 13, and 14 have been shown to participate in the healing of bone fracture (Yamagiwa et al, 1999;Gerstenfeld et al, 2003;Henle et al, 2005;Wang et al, 2006).…”
mentioning
confidence: 99%
“…It has also been postulated that remodeling of proteoglycans may contribute to tooth eruption (12,13). The present study found that the expression of ADAMTS5 decreases after 24 h by 2.1 fold, suggesting that iRoot BP may have a negative effect on the remodeling of proteoglycans which constitute the extracellular environment of the teeth.…”
Section: Discussionsupporting
confidence: 50%
“…PrP c recruits and couples to the CREB transcription factor and is involved in the transcriptional regulation of metalloproteinase MMP-9 and its inhibitor TIMP-1 in neuronal cells (Pradines et al, 2008). MMPs and TIMPs are also expressed in periodontal tissues including cementum and periodontal ligaments (Maruya et al, 2003) and involve in dentin matrix remodeling during tooth development (Goldberg et al, 2003;Sakuraba et al, 2006;Niu et al, 2011). A functional relationship of PrP c with these matrix enzymes in tooth development can be a challenging subject.…”
Section: Discussionmentioning
confidence: 99%